Program Air Tanah Berkelanjutan Melalui Diseminasi Berbasis Hologram dan WebGIS di Kelurahan Bandarharjo Kota Semarang: Sustainable Groundwater Program Through Hologram and WebGIS Based Dissemination in Bandarharjo Village, Semarang City - Fajar Wahyushi Fuedsi; Cahaya Pramudita; Astria Rachmadani; Muhammad Hasan Mustofa; Vina Nurul Husna; Evin Yulianto (Educate: Journal of Community Service in Education, 2024)
The increasingly serious land subsidence in Semarang City, especially Bandarharjo Village, has become a major concern in environmental conservation efforts and the relocation of the area. From various sources, the main factor causing land subsidence in Bandarharjo Village is excessive use of groundwater. In order to mitigate land subsidence in Bandarharjo, the author conducted community service with a dissemination approach, involving various parties in Bandarharjo to work together in mitigating land subsidence. Community service (PkM) was carried out using mentoring and collaboration methods between the PkM team, the community, and stakeholders in Bandarharjo Village. In this mitigation, the PkM team utilized hologram and webGIS technology. Holograms were used as interactive presentation media during dissemination, visualizing the causes of land subsidence to the impact of land subsidence in the local area while webGIS was used as a medium for mapping groundwater use in Bandarharjo Village. In addition, the PkM team also conducted training in making biopores, which were placed at several points in Bandarharjo. Tree planting is also carried out in order to mitigate land subsidence. From the results of the community service that has been carried out, it has increased the knowledge and skills of the Bandarharjo community in efforts to mitigate land subsidence.